2022
DOI: 10.1039/d2nj03739d
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering of a tri-phase CoFe/CoFeOx/Co–Fe3O4electrocatalyst for promoting the oxygen evolution reaction

Abstract: Exploration of high-efficient and structurally stable electrocatalysts for electrocatalytic oxygen evolution reaction (OER) at anode by a simple and feasible strategy is remained challenging for achieving hydrogen production with low-energy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…S7, ESI†) demonstrated that the IrO x /WO 3 could be the first-echelon electrocatalysts in OER catalysis. 28–30 In addition, at the overpotential of 350 mV, the delivered current density of IrO x /WO 3 (315.0 mA cm −2 ) could be 300 times that of IrO x /WO 3 · x H 2 O (1.1 mA cm −2 ) and 15 times that of commercial IrO 2 (22.0 mA cm −2 ). Meanwhile, as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…S7, ESI†) demonstrated that the IrO x /WO 3 could be the first-echelon electrocatalysts in OER catalysis. 28–30 In addition, at the overpotential of 350 mV, the delivered current density of IrO x /WO 3 (315.0 mA cm −2 ) could be 300 times that of IrO x /WO 3 · x H 2 O (1.1 mA cm −2 ) and 15 times that of commercial IrO 2 (22.0 mA cm −2 ). Meanwhile, as shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…3,4 Despite Ru and Ir (including their oxides) being ideal catalysts for the OER, their high-cost and poor stability not only hinder their commercial application but also lead to the development of cost-effective catalysts, such as transition metal compounds. [5][6][7] Among various catalysts, heterogeneous transition metal oxide (TMOs) and nitride (TMNs) catalysts, including NiO/ CoN, 8 Ni 3 Mo 3 N-MoO 2 -NiO, 9 and CoO/CoN, 10 have been reported as OER catalysts. 11,12 This is because the TMOs are suitable for water adsorption, 13 while TMNs exhibit better electronic conductivity than the transition metal oxides.…”
mentioning
confidence: 99%